(untitled) (The Peerian Journal, 2023)
In this article, it is stated that educating young people in the spirit of faith, devotion to the national goal, kindness to each other, respect for the Motherland, nation, religion, language, history, and cultural traditions is a requirement of today’s modern day. Information is given about the pedagogical technologies that should be put on the way to the goal of wide use of our traditions and ancient traditions for the education of our students in the education system.